If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -108 + 9y + 108 = 19683 + -38a + -76 Reorder the terms: -108 + 108 + 6x + 9y = 19683 + -38a + -76 Combine like terms: -108 + 108 = 0 0 + 6x + 9y = 19683 + -38a + -76 6x + 9y = 19683 + -38a + -76 Reorder the terms: 6x + 9y = 19683 + -76 + -38a Combine like terms: 19683 + -76 = 19607 6x + 9y = 19607 + -38a Solving 6x + 9y = 19607 + -38a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 6x + 9y + -9y = 19607 + -38a + -9y Combine like terms: 9y + -9y = 0 6x + 0 = 19607 + -38a + -9y 6x = 19607 + -38a + -9y Divide each side by '6'. x = 3267.833333 + -6.333333333a + -1.5y Simplifying x = 3267.833333 + -6.333333333a + -1.5y
| 5(x-7)-2(x+1)=23 | | 420x=110x | | 40-5u=3u | | 5x+8x-3x-5=25 | | 25+4(3+a)=5 | | 40-5u=30 | | 27.3=3/4c | | 4u=81-5u | | 2r+9=11 | | 5(4y+2)=40 | | 594/12 | | 1.20x+2.40y=232 | | x+y=7.3 | | 8y+18=98 | | 1/12y-4=-12 | | 2x-10+5x=31 | | Y-17=21 | | -3h(w+4)=4w-5 | | 8(n+1)+3=45 | | 7(12-x)=3x+18 | | 7(n+1)+3=45 | | 5z+11z=7y | | (2x^2-8x-18)/(2x-4)^2 | | 13=x+8+x+11 | | G+8=235 | | 6(n+1)+3=45 | | 0=9x^4-48x^2+64 | | 2x+4-x=17 | | 6x-2=20whatisx | | 317+x=360 | | 2[n+26]=264 | | (5+3d)+(8+2n)= |